INNOVATION FOR INCLUSIVE DEVELOPMENT: MAPPING AND AUDITING THE USE OF ICTS IN THE SOUTH AFRICAN PRIMARY EDUCATION SYSTEM - Hove, Precious; Grobbelaar, Sara (South African Journal of Industrial Engineering, 2020)
Inclusive education aims to identify and minimise barriers to learning and maximise learner participation in the education system. With a focus on the use of information and communication technologies in the South African primary education system, this study aims 1) to create a framework with which to evaluate the current state of ICT uptake across core functions for a school; 2) to audit the current state of innovation uptake; 3) to use the audit outcomes to identify challenges to the uptake of ICTs; and 4) to identify measures for facilitating an improved uptake of these innovations. The researchers conclude that a need exists for government to ensure consistent ICT uptake and use throughout the education system through a better implementation of standards, policies, and processes that facilitate technology uptake.